Dimensi Metrik Lokal pada Operasi Korona Graf Ular Segitiga dengan Graf Lintasan Orde Dua - Zuha, Jaqueline Widad; Rahmadi, Deddy; Munandar, Arif (Program Studi Matematika, Universitas Nusa Cendana, 2026)
Graphs were first introduced by Leonard Euler through the Königsberg Bridge problem in 1736. Let G be a connected graph with vertex set V(G) and edge set E(G). The concept of distance in graphs leads to the notions of metric dimension and local metric dimension. Let W V(G) with W = {w_1, w_2, …, w_n}. The representation of a vertex x V(G) with respect to W is defined by r(x W) = (d(x, w_1), d(x, w_2), …, d(x, w_n)). The set W is called a local resolving set of G if for every pair of adjacent vertices u, v V(G), r(u W) r(v W). The minimum cardinality of such a set is called the local metric dimension of G and is denoted by _(G). This research aims to determine the metric dimension and local metric dimension of the triangular snake graph T_n, as well as graphs obtained from the corona operation between T_n and a path graph of order two. The method used is a literature study with an analysis of graph structure and vertex distances. The results show that both the metric dimension and the local metric dimension of the triangular snake graph are equal to 2. Moreover, the local metric dimension of T_n P_2 is 2n+1, while that of P_2 T_n is n+3 for odd n and n+2 for even n.